2016
DOI: 10.1037/apl0000097
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear effects of team tenure on team psychological safety climate and climate strength: Implications for average team member performance.

Abstract: The teams literature suggests that team tenure improves team psychological safety climate and climate strength in a linear fashion, but the empirical findings to date have been mixed. Alternatively, theories of group formation suggest that new and longer tenured teams experience greater team psychological safety climate than moderately tenured teams. Adopting this second perspective, we used a sample of 115 research and development teams and found that team tenure had a curvilinear relationship with team psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 119 publications
7
88
2
Order By: Relevance
“…Hypothesis 6 stated that the indirect curvilinear relationship between benevolent leadership and team performance through team action processes would be contingent upon team commitment. To test this curvilinear moderated mediation model, we again used the Monte Carlo method (Koopmann, Lanaj, Wang, Zhou, & Shi, ; Preacher et al., ) with 20,000 bootstrap replications. Results demonstrated that the indirect curvilinear relationship between benevolent leadership and team performance via team action processes was only significant when team commitment was low, not high.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypothesis 6 stated that the indirect curvilinear relationship between benevolent leadership and team performance through team action processes would be contingent upon team commitment. To test this curvilinear moderated mediation model, we again used the Monte Carlo method (Koopmann, Lanaj, Wang, Zhou, & Shi, ; Preacher et al., ) with 20,000 bootstrap replications. Results demonstrated that the indirect curvilinear relationship between benevolent leadership and team performance via team action processes was only significant when team commitment was low, not high.…”
Section: Resultsmentioning
confidence: 99%
“…The central theoretical rationale underlying the curvilinear relationship between benevolent leadership and team performance rests on the argument that excessive benevolence can undermine a team's goal‐striving processes. Specifically, we have proposed that by allocating most of one's personal resources to attending to subordinates’ personal needs, excessively benevolent team leaders would necessarily have less time and energy to coordinate task‐oriented team activities, such as tracking progress toward goals, managing team resource use, and monitoring team member interactions (Bergeron et al., ; Koopman et al., ). Building on Study 1, in Study 2, we seek to explicitly test this idea, by examining whether team goal‐striving activities—specifically, team action processes—mediate the focal curvilinear relationship between benevolent leadership and team performance.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The scale assesses intragroup trust and perceived fairness and trust in the department’s dispute resolution and conflict management procedures, including trust in managers’ conflict management skills. These scales have been used in numerous studies, and researchers have reported the scales as reliable with Cronbach’s alpha of 0.81 for climate for conflict management ( Zahlquist et al, 2019 ), Cronbach’s alpha of 0.86 1 for climate for psychological safety ( Koopmann et al, 2016 ), and Cronbach’s alpha of 0.92 2 for intragroup conflict ( Jehns, 1995 ). Example items are “The management handles cases of conflicts well” (conflict management climate), “It is easy to address problems and difficult issues in my work team” (intragroup trust), and “There is jealousy and rivalry between members of my work team” (intragroup conflict).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The group formation literature suggests that team tenure has a curvilinear effect on team psychological safety climate, defined as "shared perceptions that the team is safe for interpersonal risk taking, " which in turn influences team performance (Koopmann, Lanaj, Wang, Zhou, & Shi, 2016, p. 940). A newly formed team, including a TMT, is likely to focus on the development of trust and the creation of a common group identity, which facilitate positive perceptions of similarities among team members (Koopmann et al, 2016;McKnight, Cummings, & Chervany, 1998). In abruptly dynamic environments, a TMT must make high-stakes decisions in a timely manner and share risks collectively.…”
Section: Findings and Discussionmentioning
confidence: 99%